(untitled) (Bangladesh Journal of Pharmacology, 2018)
The aim of this meta-analysis was to systematically evaluate the efficacy and safety of novel oral anticoagulants and vitamin K antagonists in the treatment of venous thromboembolism. A total of 6 studies met the inclusion criteria and a total of 19,350 patients with venous thromboembolism were included. Among them, rivaroxaban (3 RCTs, n=90/3,449/4,832); dabigatran (2 RCTs, n=200/2,539); edoxaban (1 RCT, n=8,240). The results of meta-analysis showed that the total bleeding rate after treatment with the vitamin K antagonist group was higher than with the new oral anticoagulant group (OR=0.82, 95% confidence interval 0.75-0.90, p<0.0001), and the difference was highly statistically significant. Overall, new oral anticoagulants are compara-ble to vitamin K antagonists, but new oral anticoagulants can reduce the occurrence of bleeding events and the safety was superior to vitamin K antagonists.